Investigation of the transability of dietary small non-coding RNAs to animals - Norouzi, Milad; Bakhtiarizadeh, Mohammad Reza; Salehi, Abdolreza (Frontiers in Genetics, 2022)
Our daily diet not only provides essential nutrients needed for survival and growth, but it also supplies bioactive ingredients to promote health and prevent disease. Recent studies have shown that exogenous microRNAs (miRNAs), xenomiRs, may enter the consumer’s body through dietary intake and regulate gene expression. This fascinating phenomenon suggests that xenomiRs can act as a new class of bioactive substances associated with mammalian systems. In contrast, several studies have failed to detect xenomiRs in consumers and reported that the observed diet-derived miRNAs in the previous studies can be related to the false positive effects of experiments. This discrepancy can be attributed to the potential artifacts related to the process of experiments, small sample size and inefficient bioinformatics pipeline. Since this hypothesis is not generally accepted yet, more studies are required. Here, a stringent and reliable bioinformatics pipeline was used to analyze 133 miRNA sequencing data from seven different studies to investigate this phenomenon. Generally, our results do not support transfer of diet-derived miRNAs into the animal/human tissues in every situation. Briefly, xenomiRs were absent from most samples and also their expressions were very low in the samples where they were present, which is unlikely to be sufficient to regulate cell transcripts. Furthermore, this study showed that the possibility of miRNAs being absorbed through animals' diets and thus influencing gene expression during certain periods of biological development is not inconceivable. In this context, our results were in agreement with the theory of the transfer of small RNAs under certain conditions and periods, as xenomiRs were found in colostrum which may modulate infants' immune systems via post-transcriptional regulation. These findings provide evidence for the selective absorption of diet-derived small RNAs, which need to be investigated in future studies to shed light on the mechanisms underlying the transference of diet-derived miRNAs.